Panspinal Epidural Abscess: A Devastating Complication of Group B Streptococcal Bacteremia - Rehmat Ullah Awan; Ambreen Nabeel; Mohammed Alsaggaf (Case Reports in Infectious Diseases)
Background. SEAs are infrequent; however, panspinal infections are even rarer, especially when GBS infection is involved. The cornerstone of treatment is based on early diagnosis and use of targeted antimicrobial therapy; in case of cord compression or neurological compromise, urgent surgical intervention should be pursued. Overall, it is an infrequent condition and therefore requires prospective multicenter studies. Case Presentation. We describe a case who presented with diabetic lower extremity wounds; however, soon the patient developed bowel and bladder incontinence in the setting of back pain, secondary to panspinal epidural abscess. The patient’s case is unique in two aspects: firstly, it is panspinal, and secondly, its causative agent is GBS. Conclusion. Prompt diagnosis of SEA is critical in the preservation of neurological function. Anyone presenting with fevers, back pain, and neurological changes should have urgent MRI evaluation of the spine.